Longitudinal associations between childhood and adulthood externalizing and internalizing psychopathology and adolescent substance use. Issue 8 (13th September 2013) - Miettunen, J.; Murray, G. K.; Jones, P. B.; Mäki, P.; Ebeling, H.; Taanila, A.; Joukamaa, M.; Savolainen, J.; Törmänen, S.; Järvelin, M.-R.; Veijola, J.; Moilanen, I.
Abstract : Background: Emotional and behavioral problems are commonly associated with substance use in adolescence but it is unclear whether substance use precedes or follows mental health problems. The aim was to investigate longitudinal associations between externalizing and internalizing psychopathology and substance use in a prospective population study design. Method: The sample was the Northern Finland Birth Cohort 1986 Study (NFBC 1986; n = 6349; 3103 males). Externalizing and internalizing mental health problems were assessed at age 8 years (Rutter scales), substance use and externalizing and internalizing problems [Youth Self-Report (YSR)] at age 15–16 years, and hospital diagnoses for internalizing disorders (age 25) and criminal offences (age 20) from nationwide registers in adulthood. Results: Externalizing problems at age 8 were associated with later substance use. After adjustment for sociodemographic factors, parental alcohol use and psychiatric disorders, and earlier externalizing and internalizing problems, substance use predicted criminality, especially among males, with the highest odds ratio (OR) for cannabis use [adjusted OR 6.2, 95% confidence interval (CI) 3.1–12.7]. Early internalizing problems were not a risk for later substance use. Female adolescent cannabis (OR 3.2, 95% CI 1.4–7.3) and alcohol (OR 2.1, 95% CI 1.1–4.2) use predicted internalizing disorders in adulthood. Conclusions: Externalizing problems precede adolescent substance use in both genders, whereas, among boys, substance use also precedes criminal offences. Internalizing problems may follow substance use in females. These associations were robust even when taking into account previous mental health problems.